Subjectivity and its Others - Ivaldo, Marco (Acta Philosophica, 2014)
The aim of this contribution is to present some conditions for a critical resumption of the concept of subjectivity in our time. In this sense, I try to develop the potentiality of the transcendental philosophy of Fichte and the close connection which according to him must exist between the theoretical side, the intelligence, and the practical side, the will, of the human subject. Subjectivity is not an isolated individuality, but should be understood within the relationship with its “others”. A decisive feature of subjectivity is the freedom understood as a formative principle of experience. The transcendental subjectivity is not the ground of being, but is the manifestation of an absolute principle, that can be affirmed in philosophy in an indirect way.